Inspirasi Grand Trianonin Versailles Pada Busana Pesta Bertema Aristocrachy - Norma Hamidah; Suhartini, Ratna (Universitas Negeri Surabaya, 2025)
The right source of ideas plays an important role in designing party wear that is not only visually appealing but also deeply incorporates cultural and historical values. This research aims to describe the process and final results of party wear inspired by the Grand Trianon, a classical-style palace in the Versailles complex, France. The visual elements of the Grand Trianon are translated into party wear through fabric manipulation techniques such as cross tucks, tucks of equal width, cording, and brocade fabric application techniques. The method used is the Double Diamond Model, which consists of four stages: discover, taking the heritage theme with the sub-theme of aristocracy from Indonesian Trend Forecasting 2024 & 2025. Define, visual elements are collected into a moodboard. Develop, develop 5 women's party wear and 5 men's party wear. Deliver, the developed designs received feedback from fashion experts. The finished party wear with an aristocracy theme inspired by the Grand Trianon has met the plan, consisting of a 3-piece women's party wear including a gown, crop bolero, and detachable sleeve embellishments, complemented with accessories. The men's party attire consists of a double-breasted suit that completed with a lapel brooch, shirt, trousers, belt, and sash, reflecting a classic, elegant, and representative impression in line with the aristocracy theme.